Accumulation of microplastics and Tcep pollutants in agricultural soil: Exploring the links between metabolites and gut microbiota in earthworm homeostasis. (December 2022) - Cao, Jing; Wang, Qian; Lei, Yumeng; Jiang, Xiaofeng; Li, Mei
Graphical abstract: Highlights: An abundant of MP and Tcep was occurred in soil at vegetable plastic greenhouses. Small-sized MPs and Tcep co-exposure enhanced toxicity to earthworm. Gut microbiota play important role in metabolic homeostasis in earthworm. MPs and their additives pollution posed potential risks to soil ecosystems. Abstract: Agricultural soil contamination with plastic film has become a critical global environmental problem, requiring greater research on the possible occurrence and biological risk of microplastics (MPs) and their additives in soil ecosystems. The presence of MPs and tris (2-chloroethyl) phosphate (Tcep) in agricultural soil was investigated at nine sites in the present study. Polyethylene MPs (PE-MPs) and Tcep were found at all nine sites. To study co-exposure effects on soil microbiota and earthworms, and to mimic a realistic exposure scenario, 0.05 % (w/w) PE-MPs with three particle size ranges were combined with Tcep (1.0 mg/kg). After 28 days of exposure, there was no indication that added PE-MPs and/or Tcep significantly affected the soil microbial community structure. In earthworms, size-selective intake, digestion and egestion of PE-MPs may occur, with Tcep co-exposure affecting the residual Tcep concentration in earthworm intestines (3.52–9.31 μg/g dw). Long-term earthworm PE-MPs intake caused intestinal damage, and Tcep co-exposure increased oxidative stress, thereby influencing their feeding behavior and growth, resulting in weight loss (3.42 %–14.96 %), especially for the most common PE-MPs sizes (0–300 μm). High performance liquid chromatography-mass spectrometry (LC-MS) was used for metabolomic analysis, revealing the significant up-regulation of citrate ( p  < 0.001) and down-regulation of l -glutamate ( p  < 0.05) in co-exposure groups. Co-exposure resulted in the alteration of most metabolic pathways, thereby impairing nervous, digestive and excretory systems in the earthworm, with an associated decrease in amino acid metabolism and changes in tricarboxylic acid (TCA) cycle intermediates. Gut microbiota, such as Proteobacteria ( Verminephrobacter and Bradyrhizobium ) and Firmicutes ( Bacillus ), are critically important in maintaining earthworm metabolic homeostasis, particularly for the TCA cycle and amino acid metabolism. Overall, MPs and Tcep co-exposure in agricultural soil enhanced their toxicity to earthworms and may potentially endanger the development of agricultural sustainability.